Monetary policy instruments in the system of adjustment of external payments imbalances - Мироненко, Григорій Вікторович (Technology audit and production reserves, 2014)
A brief overview of theoretical concepts of adjustment of external payments imbalances and analysis of the role of monetary policy instruments in the conditions of transformation of monetary policy in Ukraine are given in the paper. The relevance of the study, in the author’s opinion, is justified by several factors: firstly, the existing research work mostly covers the period of using a fixed exchange rate in Ukraine, while the effects of switching to inflation targeting, transition to the national currency floating and increased use of other monetary policy instruments are underinvestigated; secondly, the economic crisis of the 2007-2008th, the economic recession in the post-crisis period, threatening growth dynamics of the current account deficit and change of monetary policy targets, declared by the National Bank of Ukraine resume the relevance of the balance of payments equilibration. During the study the author has concluded that stabilization measures of the NBU, which are to diversify the instruments of monetary policy of the National Bank of Ukraine in the I quarter of the 2014, namely to abandon the fixed exchange rate and currency interventions, increase the use of interest rate policy have proved to be effective.